2017
DOI: 10.5812/jjm-13108
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Biofilm Production and Presence of Attachment Factors in Human Uropathogenic Strains of Escherichia coli

Abstract: Background: Escherichia coli is one of the most common causes of different infections. Biofilm structure allows the strains to persist on the biotic and abiotic surfaces for a long time and impairs eradication. Surface colonization of E. coli could be done with several extracellular appendages, which are effective productive events leading to biofilm maturity. Objectives: In this study, the possible relationship between the presence of fimA (encoding large subunit of Type I fimbriae) and csgA (encoding curli f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Approx. 27 E. coli and 13 K. pneumoniae isolates were found to possess more than one biofilm-producing gene in this study which was also supported by Bakhtiari and Javadmakoei (2017) and Banerjee and Acharyya (2020).…”
Section: Resultssupporting
confidence: 71%
“…Approx. 27 E. coli and 13 K. pneumoniae isolates were found to possess more than one biofilm-producing gene in this study which was also supported by Bakhtiari and Javadmakoei (2017) and Banerjee and Acharyya (2020).…”
Section: Resultssupporting
confidence: 71%
“…Based on the results of Qin, the prevalence of csgA genes in UPEC isolates and commensal E. coli isolates was 30% and 34%, respectively, indicating no significant differences between the isolates (43). In another study, Bakhtiari et al demonstrated that 33 out of 35 UPEC isolates had csgA gene while they found no correlation between the presence of csgA and biofilm production ability since most of the isolates with or without biofilm production ability had csgA gene (44). Similarly, Rijavec et alobserved no association between usp, papC, and sfa/foc virulence genes and biofilm production in pathogenic E. coli (45).…”
Section: Discussionmentioning
confidence: 99%
“…They recommended the BHI medium containing 1% sucrose for the study of biofilmproducing ability of these strains (32). In a study by Rijavec et al biofilm production by pathogenic E. coli had no correlation with the presence of papC, usp, and sfa/foc virulence genes.…”
Section: Discussionmentioning
confidence: 99%